2012
DOI: 10.5539/elt.v5n11p16
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Reflective Learning Portfolios and Dialogue Journal Writing on Iranian EFL Learners’ Accuracy in Writing Performance

Abstract: This study aimed at comparing the effects of reflective learning portfolio (RLP) and dialogue journal writing (DJW) on the Iranian EFL learners' grammatical accuracy in writing as well as their overall writing performance. 60 Iranian EFL learners between the ages of 17 to 30 who were studying at general English courses were selected based on their performance on the Nelson English Language Test. They were assigned randomly into two experimental groups: DJW and RLP. Each group received 14-sessions of treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Moreover, because the learners in this study were required to revise their written papers based on the feedback they received, this could have made them attend to their errors and increase their level of attention and reflection; therefore, the finding of this study also support the researchers who demonstrated the effectiveness of reflection in their studies (e.g., Hemmati & Soltanpour, 2012;Soltanpour & Valizadeh, 2017). In addition, the finding of this study supports the previous studies which supported the effectiveness of indirect WCF (Karm & Nassaji, 2020).…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, because the learners in this study were required to revise their written papers based on the feedback they received, this could have made them attend to their errors and increase their level of attention and reflection; therefore, the finding of this study also support the researchers who demonstrated the effectiveness of reflection in their studies (e.g., Hemmati & Soltanpour, 2012;Soltanpour & Valizadeh, 2017). In addition, the finding of this study supports the previous studies which supported the effectiveness of indirect WCF (Karm & Nassaji, 2020).…”
Section: Discussionsupporting
confidence: 63%
“…This way, the researchers would be able to check if either of the methods were effective in improving writing performance. Hemmati and Soltanpour (2012) found a greater gain of grammatical accuracy in writing as well as overall writing performance in participants who were exposed to reflective learning portfolios (RLP) than those who wrote dialogue journals during a fourteen-session treatment. The authors discussed that RLP necessitates intentional reflection scaffolding by a collaborator while dialogue journal writing requires incidental learning in which the instructor "responses without referring explicitly to the errors" (Ibid, p. 22).…”
Section: Empirical Findingsmentioning
confidence: 96%
“…The portfolio must include the students' participation in selecting contents, the criteria for selection, and the evidence of student selfreflection. It involves learners in continuous reflection and collaboration, focusing on selective evidence of learning (Hemmati & Soltanpour, 2012), making students evaluate themselves and monitor their progress over time (Zubizarreta, 2009). Moreover, the portfolio can have different forms, such as written text, electronic display, or other creative projects (Zubizarreta, 2008).…”
Section: Reflective Learning Portfolio and Dialogue Journal Writingmentioning
confidence: 99%
“…Foreign language writers usually encounter a significant challenge in developing their writing skills (Evans et al, 2010). The teachers' main challenge in teaching writing is seeing that learners learn from their previous mistakes and acquire writing fluency and accuracy (Hemmati & Soltanpour, 2012).…”
Section: Introductionmentioning
confidence: 99%